2019
DOI: 10.1021/acs.jpcc.9b10308
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Stimulated Raman Spectroscopy Reveals the Phosphate Network in the Amorphous Cobalt Oxide Catalyst and Its Role in the Catalyst Formation

Abstract: Amorphous oxides are one of the most active catalysts for the oxygen evolution reaction (OER). However, very little is known about the structure of the amorphous oxide catalyst during OER, especially the structural detail of the low-atomic number groups (e.g., O, P-containing species). Herein, we report in situ stimulated Raman spectroscopy (SRS) of an amorphous cobalt oxide deposited in phosphate electrolyte (CoPi), one of the most active OER catalysts in neutral pH. In situ SRS reveals the presence of orthop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 60 publications
(116 reference statements)
0
12
0
Order By: Relevance
“…64 The polyphosphates, which likely surround the Co-oxo clusters, can form a hydrogen-bond network, which likely favors proton transport inside the catalyst material. 63,65,66 On the contrary, the 990 cm −1 solution-peak (dotted black line) has no visible correspondence in the dry-CoCat spectrum, suggesting that phosphate is present inside the CoCat film mainly in the H 2 PO 4 − form. To test the assignment of these bands to phosphate, we changed the deposition solution from KPi to KBi buffer at pH 9.2.…”
Section: A Raman Spectra Of Amorphous Cooxmentioning
confidence: 99%
See 1 more Smart Citation
“…64 The polyphosphates, which likely surround the Co-oxo clusters, can form a hydrogen-bond network, which likely favors proton transport inside the catalyst material. 63,65,66 On the contrary, the 990 cm −1 solution-peak (dotted black line) has no visible correspondence in the dry-CoCat spectrum, suggesting that phosphate is present inside the CoCat film mainly in the H 2 PO 4 − form. To test the assignment of these bands to phosphate, we changed the deposition solution from KPi to KBi buffer at pH 9.2.…”
Section: A Raman Spectra Of Amorphous Cooxmentioning
confidence: 99%
“…At these concentrations, phosphate starts forming dimers or polymers forming a hydrogen-bond network, which, in the CoCat, can be functional for proton transport. 63,65,66…”
Section: A Raman Spectra Of Amorphous Cooxmentioning
confidence: 99%
“…The results of Raman spectra confirm that V element is successfully introduced. The strength of M−O bonds are very weak, which indates amorphous structure of CoV−Pi catalyst [29] . The bonding nature of CoV−Pi, CoV−O, Co−Pi and Co 3 O 4 was analyzed by FT‐IR spectroscopy (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…The strength of MÀ O bonds are very weak, which indates amorphous structure of CoVÀ Pi catalyst. [29] The bonding nature of CoVÀ Pi, CoVÀ O, CoÀ Pi and Co 3 O 4 was analyzed by FT-IR spectroscopy (Figure 2b). Obviously, the peak at 1037 cm À 1 indicates the vibration of P=O bond, which proves the existence of phosphate groups.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…66 Eom et al reported that structural information and formation mechanism of amorphous cobalt oxides in phosphate electrolyte (CoPi) could be successfully observed because stimulated Raman spectroscopy, which is a thirdorder non-linear phenomenon, could dramatically enhance Raman signals of the phosphate bands. 67 Further application of the nonlinear Raman spectroscopy to the electrochemical systems is expected in future studies.…”
Section: In Situ/operando Raman Spectroscopymentioning
confidence: 99%